A Robot Platform for Highly Efficient Pollutant Purification - Wang, Haocheng; Yu, Shimin; Liao, Junjie; Qing, Xudong; Sun, Daxing; Ji, Fengtong; Song, Wenping; Wang, Lin; Li, Tianlong (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, we propose a highly efficient robot platform for pollutant adsorption. This robot system consists of a flapping-wing micro aircraft (FWMA) for long-distance transportation and delivery and cost-effective multifunctional Janus microrobots for pollutant purification. The flapping-wing micro air vehicle can hover for 11.3 km with a flapping frequency of approximately 15 Hz, fly forward up to 31.6 km/h, and drop microrobots to a targeted destination. The Janus microrobot, which is composed of a silica microsphere, nickel layer, and hydrophobic layer, is used to absorb the oil and process organic pollutants. These Janus microrobots can be propelled fast up to 9.6 body lengths per second, and on-demand speed regulation and remote navigation are manageable. These Janus microrobots can continuously carry oil droplets in aqueous environments under the control of a uniform rotating magnetic field. Because of the fluid dynamics induced by the Janus microrobots, a highly efficient removal of Rhodamine B is accomplished. This smart robot system may open a door for pollutant purification.